2022
DOI: 10.3389/fmicb.2022.926724
|View full text |Cite
|
Sign up to set email alerts
|

Mixed infection of an emaravirus, a crinivirus, and a begomovirus in Pueraria lobata (Willd) Ohwi

Abstract: Pueraria lobata (Willd) (Pueraria montana var. lobata (Willd.) Maesen & S. M. Almeida ex Sanjappa & Predeep) is an important herbal medicine used in many countries. In P. lobata plants showing symptoms of mosaic, yellow spots, and mottling, mixed infection of new viruses provisionally named Pueraria lobata-associated emaravirus (PloAEV, genus Emaravirus), Pueraria lobata-associated crinivirus (PloACV, genus Crinivirus), and isolate CQ of the previously reported kudzu mosaic virus (KuMV-CQ, genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Curiously, until very recently, the only report regarding viruses affecting kudzu from Southeastern and Eastern Asia originated from Vietnam and concerned kudzu mosaic virus (KuMV, a begomovirus) [9]. However, research conducted by Liang and collaborators revealed mixed infections by three viruses in a batch of symptomatic samples collected in Beibei (Chongqing, China) [10]. Two of the viruses detected were determined to be novel viruses in the genera Crinivirus (family: Closteroviridae) and Emaravirus (family: Fimoviridae) and were observed in coinfections with KuMV.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Curiously, until very recently, the only report regarding viruses affecting kudzu from Southeastern and Eastern Asia originated from Vietnam and concerned kudzu mosaic virus (KuMV, a begomovirus) [9]. However, research conducted by Liang and collaborators revealed mixed infections by three viruses in a batch of symptomatic samples collected in Beibei (Chongqing, China) [10]. Two of the viruses detected were determined to be novel viruses in the genera Crinivirus (family: Closteroviridae) and Emaravirus (family: Fimoviridae) and were observed in coinfections with KuMV.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In figs, 15 viruses have been identified, belonging to several genera [72][73][74][75][76][77]. The recently detected Pueraria lobata-associated emaravirus (PloAEV) was shown to occur only in mixed infection with two different viruses raising questions of mutual relationships between them [61].…”
Section: Symptomatologymentioning
confidence: 99%
“…In fig, 15 viruses have been identified, belonging to several genera [36][37][38][39][40][41]. The recently detected Pueraria lobata-associated emaravirus (PloAEV) was shown to occur only in mixed infection with two different viruses raising questions of mutual relationships between them [42]. The complexity of viruses in different combinations can induce a variety of symptoms with synergistic or antagonistic effects in their hosts, thereby impeding the determination of which symptom is caused by which virus.…”
Section: Symptomatologymentioning
confidence: 99%
“…With only few exceptions, emaraviruses seem to establish long-lasting infections in a restricted number of host species, mainly comprising of a single genus. However, transmission to experimental herbaceous plants including Arabidopsis thaliana, Nicotiana (N.) benthamiana, N. tabacum, N. clevelandii, Phaseolus vulgaris, Chrozophora rottleri and various cucurbit species was demonstrated by mechanical means for pigeonpea-infecting emaraviruses [27], RLBV [48], AcCRaV [52], TiRSaV [57], PerMV [61], LiCRaV [62], RRV [93] and PloAEV [42]. In greenhouse experiments, several sweet grasses were reported to be infected with HPWMoV [94].…”
Section: Host Rangementioning
confidence: 99%
See 1 more Smart Citation